PENGARUH KOMITMEN ORGANISASI, PROFESIONALISME DAN KOMPETENSI GURU TERHADAP KINERJA GURU DI SMPN I IDI KABUPATEN ACEH TIMUR - Suriani . (Universitas Islam Sumatera Utara, 2020)
The superiority of a nation no longer rests on natural wealth, but on the superiority of human resources, one of which is the teaching staff (teachers) who are able to answer challenges very quickly. Education is basically an effort to develop human resources, although efforts to develop human resources are not only carried out through education, especially formal education or schools, but until now, education is still seen as a means and vehicle for developing human resources that is carried out systematically , programmatic, and tiered. Performance is an outcome that must be done by a teacher to produce students so that a teacher's professionalism and teacher competence are supported by organizational commitment. Yan Kinerjag becomes the problem in this research is How the influence of Organizational Commitment, Professionalism and Teacher Competence on Teacher Performance in IDI Middle School, East Aceh Regency. As for the results of this study Performance = 19,768 +, 110 X1 +, 118 X2 +, 349 X3 Based on the results of these equations, an explanation can be described as follows: Constant value of 19.768 gives the meaning that if overall the value of variables Organizational Commitment, Professionalism and Teacher Competence) increase by 1a respectively, the value of Performance (Y) will rise to 19,768. The coefficient value of Organizational Commitment of 0.110 means that if the value of Organizational Commitment increases by 1a, the value of performance will also increase by 0.110. A positive coefficient value means that Organizational Commitment has a positive influence on Performance. Professionalism coefficient value of 0.118 means that if the value of Professionalism increases by 1a, the performance value will also increase by 0.118. A positive coefficient value means that Professionalism has a positive influence on Performance. The Teacher Competency coefficient value of 0.349 means that if the Teacher Competency value increases by 1a, the performance value will also increase by 0.349. A positive coefficient value means that Teacher Competence has a positive influence on Performance.